Prevalence and determinants of misclassification of the risk of recurrence of differentiated thyroid cancer after the first 131I post-therapeutic scintigraphy - Wongsurawat, Nantaporn; Somboonporn, Charoonsak; Raruenrom, Yutapong; Thinkhamrop, Bandit (Asia-Pacific Journal of Science and Technology, 2021)
131I total body scintigraphy has long been used for imaging the extent of disease in differentiated thyroid cancer (DTC). Currently, the risk of recurrence of DTC is stratified into low-, intermediate-, and high-risk based on pathological findings. In practice, 131I post-therapeutic scintigraphy after the first 131I treatment tends to detect additional cervical lymph node metastasis and/or distant functioning metastasis, which can guide the treatment, hence having a high impact on clinical outcome. The aim of our study is, therefore, to explore the prevalence of misclassification of the risk stratification system after the first dose of 131I therapy and to determine the factors associate with it. Misclassification was defined as the difference of the risk stratification between the one based on pathological findings and the other based on 131I post-therapeutic scintigraphy. Total of 360 patients was included. Of these, 57 patients were misclassified (15.8%). That is, 39 (10.8%) in the low-risk group should be in the intermediate group, 2 (0.6%) patients in the low-risk group should be in the high risk, and 16 (4.4%) patients in the intermediate group should be in the high-risk group. The baseline stimulated thyroglobulin (Tg) level of ≥ 10 ng/mL showed a strong association with the misclassification (OR=3.2, 95%CI: 1.4 to 7.5; p=0.007). In conclusion, detection of considerable number of misclassification in risk stratification of DTC has raised awareness of the under-prescription of 131I doses. Attention should be paid to patients with a high baseline stimulated Tg level of greater than 10 ng/mL.